2013
DOI: 10.1186/1471-2407-13-587
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of existing models for individualized breast cancer risk estimation in a screening program in Spain

Abstract: BackgroundThe aim of this study was to evaluate the calibration and discriminatory power of three predictive models of breast cancer risk.MethodsWe included 13,760 women who were first-time participants in the Sabadell-Cerdanyola Breast Cancer Screening Program, in Catalonia, Spain. Projections of risk were obtained at three and five years for invasive cancer using the Gail, Chen and Barlow models. Incidence and mortality data were obtained from the Catalan registries. The calibration and discrimination of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“…The BC screening programme in the Basque Country (BCSPBC) has invited more than 400,000 women since 1996. The risk factor profile of the Basque women population would be similar to the screened women population in Catalonia described by Arrospide et al [ 5 ].…”
Section: Introductionsupporting
confidence: 66%
“…The BC screening programme in the Basque Country (BCSPBC) has invited more than 400,000 women since 1996. The risk factor profile of the Basque women population would be similar to the screened women population in Catalonia described by Arrospide et al [ 5 ].…”
Section: Introductionsupporting
confidence: 66%
“…BCRAT has been extensively evaluated and is currently recommended for predicting breast cancer risk for US women undergoing mammographic screening (42,43). Whereas some studies found no evidence for miscalibration of BCRAT (44)(45)(46)(47), others reported underestimation (48)(49)(50) or overestimation (47,(51)(52)(53) of risk. Some studies reported improved calibration when using incidence and mortality rates from the same country and time period (49,50,53).…”
Section: Discussionmentioning
confidence: 94%
“…Second, we assessed model calibration by deciles of expected absolute risk and by the relative risk score. The former is commonly used in validation studies (5,(44)(45)(46)48,53,54) because absolute risk is the relevant measure for clinical or public health applications. However, strong dependence of absolute risk on age makes the differences in model performance because of other risk factors less evident than comparisons using the relative risk score, which does not include age.…”
Section: Discussionmentioning
confidence: 99%
“…The Complement of data in risk assessment of precise cancer screening is an important factor (26). Also, the meaningful use of data for personalized protocols is essential.…”
Section: Introductionmentioning
confidence: 99%